How do methane rates vary with soil moisture and compaction, N compound and rate, and dung addition in a tropical soil? - Cardoso, Abmael da Silva [UNESP]; Quintana, Bruna Giovani [UNESP]; Janusckiewicz, Estella Rosseto [UNESP]; de Figueiredo Brito, Liziane [UNESP]; da Silva Morgado, Eliane; Reis, Ricardo Andrade [UNESP]; Ruggieri, Ana Claudia [UNESP] (Springer Nature, 2018)
Soil moisture and compaction, and source of N and bovine urine can reduce methane (CH4) rates from agricultural soils. However, the magnitude of the effect is unknown in tropical soil under different conditions, as well as the potential of different urine-N concentration, volume, and sources of N in such an effect. This study aimed to investigate the effects of different soil conditions (moist, dry, compacted, moist-dung, moist-dung-compacted), N concentration in urine (2.5, 5.0, 10.0, and 15.0 g N L−1), volume of urine (25, 50, 100, and 200 ml kg−1 dry soil), and source of N (ammonium, nitrate, and urea) on CH4 emissions. A tropical Ferralsol soil from marandu-grass pasture was incubated during 106 days and the CH4 concentration determined by gas chromatography. The CH4 rates varied significantly according to the soil conditions when manipulated the urine-N (p < 0.01) and averaged 0.75, − 0.50, 1.14, 6.23, and 8.17 μg C–CH4 m−2 h−1for the moist, dry, compacted, moist-dung, and moist-dung-compacted soil, respectively, and, not responded to the level of N (p = 0.73) averaging 2.57 μg C–CH4 m−2 h−1. When evaluated, the volumes of urine cumulative CH4 averages were − 0.52, − 1.24, − 0.88, 14.48, and 18.56 μg C–CH4 m−2 h−1 for the moist, dry, compacted, moist-dung, and moist-dung-compacted, respectively. Soils were affected by soil treatments (p < 0.001) but not by urine volumes (p = 0.30). The source of N did not influence the CH4 rates (p = 0.1) averaging 0.88, − 1.26, and − 1.19 μg C–CH4 m−2 h−1 respectively, for urea, nitrate, and ammonium. The CH4 fluxes in tropical Ferralsols are controlled by the soil characteristics and dung addition.
Keywords: Carbon cycle; Ferralsol; Greenhouse gas; Nitrogen